2011
DOI: 10.1002/cbf.1751
|View full text |Cite
|
Sign up to set email alerts
|

A novel composition for in vitro and in vivo regeneration of skin and connective tissues

Abstract: The particular combination of polydeoxyribonucleotides, l-carnitine, calcium ions, proteolytic enzyme and other ingredients acts in a synergetic way in the regeneration of skin and connective tissues. This new formulation of active principles was tested in vitro as a cell and tissue culture medium and in vivo for various preparations in support of tissue regeneration. In vitro, the new blend allowed the maintenance of skin biopsies for more than 1 year in eutrophic conditions. Immunocytochemical analyses of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 82 publications
(392 reference statements)
0
8
0
Order By: Relevance
“…As observed in Figures and , the 20 skin regeneration studies were: (1) six in vitro studies on skin fibroblasts (FBs) or biopsies (Muratore et al, ; Sini et al, ; Thellung et al, ; Belletti et al, ; Pleshkanyova et al, ; Avantaggiato et al, ); (2) six in vivo studies in animal models of thermal injuries (Bitto et al, ), back skin or ischemic flap (Polito et al, ; Chung et al, ; Lee et al, ), and back full‐thickness incisions (Galeano et al, ; Altavilla et al, ) in diabetic or healthy animals; (3) in healthy or diabetic patients affected by ulcers (Kim et al, ; Squadrito et al, ; De Caridi et al, ), benign cervical lesions (Perino et al, ) or subjected to autologous skin grafts (Rubegni et al, ; De Aloe et al, ; Valdatta et al, ) (seven clinical studies). In addition, one study included in vitro and an in vivo parts regarding the effects of PDRNs in biopsies from foot ulcers of diabetic patients and back full‐thickness wounds of diabetic mice (Gennero et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As observed in Figures and , the 20 skin regeneration studies were: (1) six in vitro studies on skin fibroblasts (FBs) or biopsies (Muratore et al, ; Sini et al, ; Thellung et al, ; Belletti et al, ; Pleshkanyova et al, ; Avantaggiato et al, ); (2) six in vivo studies in animal models of thermal injuries (Bitto et al, ), back skin or ischemic flap (Polito et al, ; Chung et al, ; Lee et al, ), and back full‐thickness incisions (Galeano et al, ; Altavilla et al, ) in diabetic or healthy animals; (3) in healthy or diabetic patients affected by ulcers (Kim et al, ; Squadrito et al, ; De Caridi et al, ), benign cervical lesions (Perino et al, ) or subjected to autologous skin grafts (Rubegni et al, ; De Aloe et al, ; Valdatta et al, ) (seven clinical studies). In addition, one study included in vitro and an in vivo parts regarding the effects of PDRNs in biopsies from foot ulcers of diabetic patients and back full‐thickness wounds of diabetic mice (Gennero et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The same conclusions were also reached in two other in vivo studies, conducted in genetically diabetic mice with incisions of the dorsum, where PDRN amount and way of administration were the same as the four previous ones (Galeano et al, ; Altavilla et al, ). One study, performed both in vitro, in biopsies of ulcers of diabetic patients, and in vivo in diabetic mice with back incisions, observed that the application of a cream or the infusion of PDRNs combined with l ‐carnitine, Ca ions, proteolytic enzymes and antioxidant agents increased cell viability, ECM protein production, healing, re‐epithelialization rate, and reduced MMP production (Gennero et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest expression of CK19 is in fetal basal epidermal cells and the lowest, almost negative, expression is in adults 33. CK19 is expressed in epidermal stem cells, but as the epidermal cells differentiate, the expression of CK19 is reduced and replaced by other CKs.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, in the remodeling phase, collagen is remodeled and realigned along tension lines and cells that are no longer needed are removed by apoptosis (Gennero et al 2011). However, pathological remodeling, such as scar formation, is often observed in various skin wounds.…”
Section: Paracrine Actionmentioning
confidence: 99%